2014
DOI: 10.1186/1471-2458-14-638
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and predictors of home injury hazards among toddlers in Wenzhou, China: a community-based cross-sectional study

Abstract: BackgroundHome hazards are associated with toddlers receiving unintentional home injuries (UHI). These result in not only physical and psychological difficulties for children, but also economic losses and additional stress for their families. Few researchers pay attention to predictors of home hazards among toddlers in a systematic way. The purpose of this study is firstly to describe the characteristics of homes with hazards and secondly to explore the predicted relationship of children, parents and family fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 15 publications
5
14
1
2
Order By: Relevance
“…Previous studies indicated that parents with high educational level could reduce the child’s injury rate more obviously [19,20,21]. In our study, multiple logistic regression analysis only showed that father with a college degree or above was negatively correlated with the behaviour of not wearing a seat belt.…”
Section: Discussioncontrasting
confidence: 50%
“…Previous studies indicated that parents with high educational level could reduce the child’s injury rate more obviously [19,20,21]. In our study, multiple logistic regression analysis only showed that father with a college degree or above was negatively correlated with the behaviour of not wearing a seat belt.…”
Section: Discussioncontrasting
confidence: 50%
“…In studies involving AH in general, in which no type specification was made, a statistically significant association was observed between the frequency of AH that caused injuries and age groups (25,28,31,43) . The age group with the highest frequency is the group between four and five years old (31,43) . It is found that, in general, accidents are less frequent among children under one.…”
Section: Category 1 -Proximal Social Determinants Of Healthmentioning
confidence: 96%
“…Regarding the Proximal SDHs, as for the individual characteristics, six articles evaluated the children's ethnicity/race and their correlation with AH (in general (19,25,43) ; asphyxiation/strangulation/ suffocation in bed (38) ; burn (48) ). In this context, white children were significantly more likely to have an injury by AH reported (19,25,38) , followed by Hispanic and black ethnicity (25,38) .…”
Section: Category 1 -Proximal Social Determinants Of Healthmentioning
confidence: 99%
See 2 more Smart Citations